Diagnosis and treatment of acutely hospitalised patients with suspected community-acquired pneumonia – clinical and microbiological perspectives - Cartuliares, Mariana (Dansk Tidsskrift for Akutmedicin, 2025)
This PhD thesis aimed to investigate potential improvements to the community-acquired pneumonia (CAP) diagnostic process within the first hours of acute admission. An improved diagnostic process would use rapid and precise diagnosis methods to support rational, targeted antibiotic prescriptions, preventing poor patient outcomes and antimicrobial resistance (AMR).